MRI methods for the evaluation of high intensity focused ultrasound tumor treatment: Current status and future needs. Issue 1 (22nd June 2015) - Hectors, Stefanie J.C.G.; Jacobs, Igor; Moonen, Chrit T.W.; Strijkers, Gustav J.; Nicolay, Klaas
Abstract : Thermal ablation with high intensity focused ultrasound (HIFU) is an emerging noninvasive technique for the treatment of solid tumors. HIFU treatment of malignant tumors requires accurate treatment planning, monitoring and evaluation, which can be facilitated by performing the procedure in an MR‐guided HIFU system. The MR‐based evaluation of HIFU treatment is most often restricted to contrast‐enhanced T1 ‐weighted imaging, while it has been shown that the non‐perfused volume may not reflect the extent of nonviable tumor tissue after HIFU treatment. There are multiple studies in which more advanced MRI methods were assessed for their suitability for the evaluation of HIFU treatment. While several of these methods seem promising regarding their sensitivity to HIFU‐induced tissue changes, there is still ample room for improvement of MRI protocols for HIFU treatment evaluation. In this review article, we describe the major acute and delayed effects of HIFU treatment. For each effect, the MRI methods that have been—or could be—used to detect the associated tissue changes are described. In addition, the potential value of multiparametric MRI for the evaluation of HIFU treatment is discussed. The review ends with a discussion on future directions for the MRI‐based evaluation of HIFU treatment. Magn Reson Med 75:302–317, 2016. © 2015 Wiley Periodicals, Inc.